Social Justice, Emotions, and Decoloniality in Language Teacher Education - Colombo-Gomes, Gysele da S.; Herrera , Luis Javier Pentón; Barcelos , Ana Maria F. (SOLETRAS, 2026)
Social Justice, Emotions and Decoloniality in Language Teacher Education